SIPN south: coordinating seasonal predictions of sea ice in the Southern Ocean - Massonnet, F; Ried, P; Jan Lieser; Bitz, C; Fyfe, J; William Hobbs; Kusahara, K (2018)
Like many regions of our planet, the Antarctic is currently undergoing profound environmental changes. Sea ice is a prominent element of this environment: it controls the heat, gas, mass and momentum exchanges between the atmosphere and the ocean. Sea ice has been steadily expanding in the Southern Ocean since the late 1970s but has displayed significant negative anomalies in recent years. Understanding and predicting how the sea-ice cover develops over time scales as short as a season is important not only for scientists but also for stakeholders or teams organizing field campaigns. Despite all potential applications, there has been to date no overall assessment of the capabilities of current prediction systems to forecast sea ice conditions at time scales of a season. This is the goal of SIPN South. SIPN South is a 2-yr project endorsed by the Year of Polar Prediction (YOPP) project. SIPN South aims at evaluating the skill of various forecast systems (statistical, dynamical) in predicting the regional summer conditions around the Antarctic continent. In this poster, we are presenting the very first coordinated austral sea ice prediction that will take place in February 2018 (summer sea ice minimum).